PERANAN DAERAH PERKOTAAN BAGI PEMBANGUNAN REGIONAL: PENERAPAN MODEL THUNEN YANG DIMODIFIKASIKAN DI INDONESIA - Prasetyo Soepono (Faculty of Economics and Business, Universitas Gadjah Mada, 1998)
Location theory shows how firms at first choose their respective optimal location and finally decide to locate in the same area (with the lowest isodapane) so that it forms a city, which is something that has to happen when firms want to operate efficiently and profitably. Further, von Thunen's concentric zone model shows that the determinants of land rent (level of development) are the size of an urban area and accessibility to the urban area. The size of an urban area has a positive effect on the level of development, whereas the accessibility has negative effect on the level of development. The application of that model to the U.S. economy has supported the expectation that urban areas and accessibility influence the level of development. The results of applying the Thunen model to the Indonesian economy will indicate whether the number of-cities and the sizes of cities and the number and types of roads/highways in Indonesia are already optimal or not so that the national urban development strategy in Indonesia needs to be revised or not.